Socioeconomic inequalities in access and use of skilled birth attendants during childbirth in Ghana: a decomposition analysis - Aseye Kpodotsi; Elizabeth Aku Baku; Jo Hunter Adams; Olufunke Alaba (BMC, 2021)
Abstract Background Equitable access to skilled birth attendance during delivery is vital for reducing global maternal deaths to 70 deaths per 100, 000 to achieve the Sustainable Development Goals (SDGs) by 2030. Although several initiatives have been implemented to reduce maternal mortality in Ghana, inequalities in access to skilled birth attendance during delivery still exist among women of different socioeconomic groups. This study assesses the socioeconomic inequalities in access and use of skilled birth attendants during delivery in Ghana. Methods Research was conducted through literature reviews and document reviews, and a secondary data analysis of the 2014 Ghana Demographic and Health Survey (GDHS), a nationally representative survey. A total of 1305 women aged 15-49 years, who had a live birth the year before to the survey in the presence of a skilled birth attendant were analysed using concentration indices and curves. The indices were further decomposed to identify the major socioeconomic factors contributing most to the inequalities. Results The results found that access to skilled birth attendants was more among women from rich households showing a pro-rich utilization. The decomposition analysis revealed that household wealth index, educational level of both mother and husband/partner, area of residence and mother's health insurance coverage were the major contributing factors to socioeconomic inequalities in accessing skilled birth attendants during child delivery among Ghanaian women. Conclusion This study confirms that a mother's socioeconomic status is vital to reducing maternal deaths. Therefore, it is worthy to focus attention on policy interventions to reduce the observed inequalities as revealed in the study.